Porous pavement in a cold climate - Bäckström, Magnus (Luleå, 1999)
Local disposal of stormwater can be achieved by using porous pavements instead of impermeable pavements with conventional stormwater pipes and manholes. The objective of this thesis was to analyse the performance of porous pavements during freezing, thawing, and snowmelting conditions in order to evaluate if the porous pavement is suitable for stormwater management and road construction in cold climate regions. A full-scale porous pavement construction was built in 1993/1994 in a residential area on the outskirts of Luleå, Northern Sweden (N:65°36´, E:22°13´). In-situ measurements of ground temperature, frost heave, groundwater levels, and runoff were performed. The draining function of the porous asphalt at different ambient air temperatures in the range -10 °C to +20°C was investigated in the laboratory. It was found that porous pavements have a potential to reduce meltwater runoff, avoid excessive water on the road surface during the snowmelt period, and accomplish groundwater recharge by local disposal of stormwater. The porous pavement was more resistant to freezing and frost heave than a comparable impermeable pavement. The full-scale porous pavement construction was not damaged by irregular frost heave. Thawing of porous pavement was a rapid process, which was explained by meltwater infiltration during the beginning of the snowmelt period. Godkänd; 1999; 20070403 (ysko)